Substrate Activity Screening (SAS) and Related Approaches in Medicinal Chemistry. (4th February 2016) - Gladysz, Rafaela; Lambeir, Anne‐Marie; Joossens, Jurgen; Augustyns, Koen; Van der Veken, Pieter
Abstract: Substrate activity screening (SAS) was presented a decade ago by Ellman and co‐workers as a straightforward methodology for the identification of fragment‐sized building blocks for enzyme inhibitors. Ever since, SAS and variations derived from it have been successfully applied to the discovery of inhibitors of various families of enzymatically active drug targets. This review covers key achievements and challenges of SAS and related methodologies, including the modified substrate activity screening (MSAS) approach. Special attention is given to the kinetic and thermodynamic aspects of these methodologies, as a thorough understanding thereof is crucial for successfully transforming the identified fragment‐sized hits into potent inhibitors. Abstract : Building on building blocks : SAS is a straightforward fragment‐based method with great potential for the design of enzyme inhibitors. A number of aspects require special attention in order to maximize the efficiency of this approach. These include proper design of the substrate library and screening assay, determination of adequate kinetic and thermodynamic substrate parameters, and selection of an appropriate warhead or isostere.